Management of gun shot injury in a tertiary hospital - Joshi, A (Journal of Society of Surgeons of Nepal, 2016)
Introduction: Gun shot injury is an uncommon surgical emergency . A timely and multidisciplinary management by surgical team is an essential factor in decreasing mortality and morbidity . This study highlights the multidisciplinary management of gun shot injury. Methodology: Bir hospital is a postgraduate teaching hospital under National Academy of Medical Sciences and tertiary referral center in Kathmandu. A prospective cohort study of gunshot injury was conducted during Septemeber 2015 and early outcome analysis was done. Results: There were thirteen cases of gunshot wound. The mean age of casualty was 31 years and all were male. Injury Number (n) Intervention Outcome Large intestine 3 Laparotomy Ileostomy/wound infection Perineum 1 Exploration/Debridement Loop ileostomy Bone- fracture 3 Traction/Enternal fixation/ Open reduction Internal Fixation Vertebra 1 Right hip power 3/5 Vascular- AV fistula 1 stenting Referred Brachial plexus 1 Sensory/motor deficit Neck 2 Exploration Marginal mandibular nerve palsy Elbow 1 Debridement/Split thickness skin graft There were no mortality and one case was referred. Discussion: With the multidisciplinary team approach, all the gunshot injury cases were managed with good outcome. The timely intervention by a surgical team is an essential factor for proper management of gun shot injury.